2011
DOI: 10.1016/j.beth.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy for Generalized Anxiety Disorder in Older Adults: A Preliminary Report

Abstract: Some evidence suggests that acceptance-based approaches such as Acceptance and Commitment Therapy (ACT) may be well-suited to geriatric generalized anxiety disorder (GAD). The primary goal of this project was to determine whether ACT was feasible for this population. Seven older primary-care patients with GAD received 12 individual sessions of ACT; another 9 were treated with cognitive-behavioral therapy. No patients dropped out of ACT, and worry and depression improved. Findings suggest that ACT may warrant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(98 citation statements)
references
References 45 publications
3
90
1
3
Order By: Relevance
“…This was not in accordance with the large number of studies conducted on the efficacy of ACT for treating anxiety (15)(16)(17). In most studies, it was emphasized that ACT is associated with changes in the habits as well as improvements in levels of anxiety for patients, which was maintained in a follow up.…”
Section: Discussioncontrasting
confidence: 56%
“…This was not in accordance with the large number of studies conducted on the efficacy of ACT for treating anxiety (15)(16)(17). In most studies, it was emphasized that ACT is associated with changes in the habits as well as improvements in levels of anxiety for patients, which was maintained in a follow up.…”
Section: Discussioncontrasting
confidence: 56%
“…18,[36][37][38][39][56][57][58][59][60][61][62][63][64] The total sample for the meta-analysis was N = 985 with an average age of 68.16 years (SD = 2.52).…”
Section: Study Selectionmentioning
confidence: 99%
“…Since people with interpersonal problems have rigid and inflexible models of behavior, ACT can be used as an effective therapy to improve their psychological flexibility through adopting acceptance techniques and cognitive defusion of thoughts, emotions, and beliefs (schemas) (3). Various studies have revealed the effectiveness of ACT on improving psychological problems, such as depression (24), social anxiety (25), generalized anxiety disorder (26), obsessive compulsive disorder (27), and dysfunctional marital relations (28). Therefore, given the increasing prevalence of these problems, especially among students, the importance of treatment is strongly felt in different communities.…”
Section: Introductionmentioning
confidence: 99%